FEATURES OF SONGS THAT SUPPORT THE DEVELOPMENT OF PRONUNCIATION SKILLS - Boboyorova Mehrigul,; Zulfiya Axmedova, (TADQIQOTLAR, 2026)
Annotation: This paper explores the role of songs in facilitating the learning of English  pronunciation.  It  examines  the  specific  characteristics  of  songs,  such  as rhythm,  melody,  repetition,  and  stress  patterns,  that  help  learners  improve  their pronunciation  skills.  By  analyzing  both  theoretical  perspectives  and  practical classroom  applications,  the  study  highlights  how  integrating  music  into  language teaching  can  enhance  learners’  phonetic  accuracy,  intonation,  and  overall  spoken fluency. The research also emphasizes the motivational and cognitive benefits of using songs, demonstrating that engaging with music supports both auditory perception and speech production in second language acquisition.